Habitat Larva Mansonia Spp. Di Desa Henda Kabupaten Pulang Pisau Sebagai Vektor Filariasis Di Kalimantan - Aqilah Az zahra; Arini Ratnasari; Arif Rahman Jabal; Indria Augustina (Direktorat Politeknik Kesehatan Makassar, 2025)
The number of filariasis cases in Central Kalimantan increased in 2021, with 49 cases of chronic filariasis reported. Filariasis is a chronic infectious disease caused by infection with three species of microfilariae parasites, namely Brugia malayi, Brugia timori, and Wuchereria bancrofti, transmitted by mosquitoes from five genera: Anopheles, Mansonia, Culex, Aedes, and Amigeres. The transmission of filariasis is influenced by several factors, including the presence of microfilaria-positive individuals, vector density, community behavior, and ecological factors that affect vector density. Regional characteristics also play a role as supporting factors for the reproduction of Mansonia spp. as filariasis vectors. This study aims to determine the distribution of Mansonia spp. larvae habitats and identify Mansonia spp. larvae species in Henda Village, Pulang Pisau District. The study employs a descriptive method with cross-sectional sampling techniques to identify Mansonia spp. larvae in Henda Village, Pulang Pisau District. The criteria for sampling Mansonia spp. larvae that can be reached for collection and sample size estimation in this study are all Mansonia spp. larvae found during the study based on the coordinates determined in Henda Village, Pulang Pisau District. The results of this study indicate that the habitat of Mansonia spp. larvae was found in fish ponds characterized by abundant aquatic vegetation. The number of larvae found was 35, distributed across two locations: location a = 33 larvae and location b = 2 larvae. The habitat of Mansonia spp. larvae can be found in fish ponds characterized by the presence of aquatic plants. The presence of Mansonia spp. larvae requires attention in terms of vector control efforts, particularly regarding the transmission of filariasis in Central Kalimantan. Keywords: Habitat; identification; larvae; Mansonia spp.; Henda Village